Impact of Work Life Balance on Employee Performance: A Case of Nepalese Insurance Companies - Karki, Roshan (Nepalese Journal of Economics, 2025)
This study examines the impact of work life balance on employee performance: A case of Nepalese insurance companies. Selection of employee performance is the dependent variable. The independent variables are flexible time, job sharing, leave policy, job design and work family balance. The primary source of data is used to assess the opinions of the respondents regarding the impact of work life balance on employee performance: A case of Nepalese insurance companies. The study is based on primary data with 200 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different work life balance factors affecting employee performance on Nepalese insurance companies. The result shows that flexible time has a positive impact on employee performance. It indicates that higher flexible time, higher would be the employee performance. Likewise, job sharing has a positive impact on employee performance. It indicates that higher the job sharing, higher would be the employee performance. Similarly, leave policy has a positive impact on employee performance. It indicates that better leave policy leads to increase in employee performance. Similarly, job design has a positive impact on employee performance. It indicates that increase in reward job design to increase in employee performance. Likewise, work family balance has a positive impact on employee performance. It indicates that increase in s work family balance leads to increase in employee performance.